2016
DOI: 10.1007/s40204-016-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on magnetic nanoparticles for magnetic hyperthermia

Abstract: Recent advances in nanomaterials science contributed to develop new micro- and nano-devices as potential diagnostic and therapeutic tools in the field of oncology. The synthesis of superparamagnetic nanoparticles (SPMNPs) has been intensively studied, and the use of these particles in magnetic hyperthermia therapy has demonstrated successes in treatment of cancer. However, some physical limitations have been found to impact the heating efficiency required to kill cancer cells. Moreover, the bio-safety of NPs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 97 publications
1
72
0
1
Order By: Relevance
“…However, the particle separation by a magnet is not affected. Negligible remanent magnetization and coercivity suggested that IO is a mixture of superparamagnetic and ferrimagnetic particles (>12.5 nm) (Kafrouni and Savadogo, 2016). Saturation magnetization of the IO nanoparticles was lower than that of bulk IO (M s = 76 and 92 A·m 2 /kg for γ-Fe 2 O 3 and Fe 3 O 4 , respectively) (Berkowitz et al, 1968), but sufficient enough to provide excellent manipulation by a magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…However, the particle separation by a magnet is not affected. Negligible remanent magnetization and coercivity suggested that IO is a mixture of superparamagnetic and ferrimagnetic particles (>12.5 nm) (Kafrouni and Savadogo, 2016). Saturation magnetization of the IO nanoparticles was lower than that of bulk IO (M s = 76 and 92 A·m 2 /kg for γ-Fe 2 O 3 and Fe 3 O 4 , respectively) (Berkowitz et al, 1968), but sufficient enough to provide excellent manipulation by a magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, by properly modifying their surface or using them to form magnetically responsive microspheres, the half‐life period could be noticeably elongated. Meanwhile, the uptake by macrophage cells could be greatly reduced and the accurate regional targeting could also be achieved, making the ferromagnetic particles applicable to MRI, target drug delivery, and hyperthermia . Moreover, magnetic levitation and other novel ideas have been put forward, aiming at building 3D cellular patterns in vitro and engineering complicated tissues .…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
“…Meanwhile, the uptake by macrophage cells could be greatly reduced and the accurate regional targeting could also be achieved, making the ferromagnetic particles applicable to MRI, [179,180] target drug delivery, [29,[181][182][183][184] and hyperthermia. [34,185,186] Moreover, magnetic levitation and other novel ideas have been put forward, aiming at building 3D cellular patterns in vitro and engineering complicated tissues. [187][188][189] With these improvements, ferromagnetic particles are believed to be increasingly important in biomedical researches and clinical treatments.…”
Section: Ferrofluid-based Detection Diagnosis and Therapymentioning
confidence: 99%
“…They include magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ) nanoparticles [6]. Magnetic nanoparticles play a big role in cancer detection [7][8][9], drug delivery [2,3], as well as hyperthermia treatment [10][11][12]. During the last decade, bi-magnetic core/shell nanoparticles featuring an iron core and an iron oxide (Fe 3 O 4 ) shell have become widely used [13][14][15][16][17][18][19], due to their superior magnetic properties [20,21].…”
Section: Introductionmentioning
confidence: 99%